(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2010)
There has been an important new development in the law of public sector procurement, namely the coming into force on September the 9th 2010 of the Act 34/2010 amending Public Contracts Act 30/2007. Among the main updates contained therein, we may highlight the new special causes for contract nullity, a new procedure for entering nullity claims, a new regulation for special appeals through the addition of a “Chapter VI” to the Public Contracts Act Law; the setting-up of new independent bodies for the determination of said specific appeals changes; the shifting of validity of contracts, i.e. of their enforceability, from the date of award to the date of formal registration, and lastly, the elimination of the two-phase process of provisional and final award. The real innovation consists however in the new set of rules for the aforesaid administration appeals in the field of procurement contracts: the filing of the appeal has an automatic suspending effect in order to prevent unlawful awarding,. It was an exclusive and optional nature and it is heard and solved by an independent body. Is is exclusive inasmuch as it replaces ordinary appeals, and it is optional because previous filing thereof is no longer necessary for the final lodging, if need be, of a “contentious” appeal before the high administrative courts.